Synthesis and Structure of a Ni(II) Complex Derived from Phthalic Acid and 1,10- Phenanthroline - Bi, Jian-Hong; Cheng, Xiao-Li; Huang, Zi-Xiang; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
A nickel(II) complex [Ni(TPHA)(phen)(H2O)3]Cl.H2O), where TPHA = phthalic acid and phen = 1,100phenanthroline, has been synthesized and characterized by IR, elemental analysis, and singlecrystal X-ray diffraction analysis. Crystal data: monoclinic, space group P2(I)/n with a = 7.5432(2) Å, b = 13.6549(3) Å, c = 20.1959(6) Å. β = 97.38º, V = 2062.98(9) Å3, z = 4, Dc = 1.530 mg/m3, Mr = 475.09, F(000) = 984 and μ = 3.092 mm-1. The final Rand wR are 0.0403 and 0.0904, respectively for 3645 observed reflections with I > 2σ(I). The centre nickel(II) ion is coordinated by six atoms in a prolonged octahedron geometry.